2007
DOI: 10.1080/10884600600995499
|View full text |Cite
|
Sign up to set email alerts
|

International Perspectives The Educational Experiences and Previous Orientation of Undergraduate Nursing Students in Alcohol and Drug: The English Context

Abstract: Several international and national reports have identified the need for nurses, including primary health care workers and staff in the prison health system, to receive adequate training in substance abuse education. The reports highlight the need for a systematic approach to education and training on substance abuse and the principles that underpin quality education and training. However, education about drugs and alcohol and their impact on health still find insufficient space within the nursing curriculum. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…As many authors have indicated, undergraduate nursing education content related to substance use has been largely stagnant, [42,43] and most students reported feeling unprepared to practice HR or care for PWUD. [18,[44][45][46][47] When participants expressed tension or discomfort with HR, it was when they attempted to contextualize the concept within their own lived experiences and personal beliefs. Participants at times expressed discomfort, uncertainty, and cognitive dissonance with some ideas, verbally or otherwise.…”
Section: Experiences Of Tensionsmentioning
confidence: 99%
“…As many authors have indicated, undergraduate nursing education content related to substance use has been largely stagnant, [42,43] and most students reported feeling unprepared to practice HR or care for PWUD. [18,[44][45][46][47] When participants expressed tension or discomfort with HR, it was when they attempted to contextualize the concept within their own lived experiences and personal beliefs. Participants at times expressed discomfort, uncertainty, and cognitive dissonance with some ideas, verbally or otherwise.…”
Section: Experiences Of Tensionsmentioning
confidence: 99%
“…Po podatkih Ministrstva za zdravje (2008) alkohol v svetu predstavlja šesti najpomembnejši vzrok za prezgodnjo umrljivost in obolevnost, v Evropi pa celo tretjega oziroma prvega med mladimi. Uživanje alkohola predstavlja velik zdravstveni problem mladih (Rassool, 2007). Med mladimi je alkohol najbolj razširjena droga, pri čemer poseganje po njem tudi narašča, še zlasti t. i. opijanje (Hovnik Keršmanc, 2010).…”
Section: Uvodunclassified
“…According to the Ministry of Health (2008), alcohol consumption is the world's sixth largest risk factor for untimely morbidity and mortality worldwide, while in Europe it ranks the third, or the first among youth. Alcohol consumption of the young is a major public health concern (Rassool, 2007). Alcohol is the most commonly misused substance associated with different types of diseases and conditions.…”
Section: Introductionmentioning
confidence: 99%